The Effect of Altitude on Broiler’s Litter Microbical Quality that Cultivated at Closed House - Cahya Setya Utama; Bambang Sulistiyanto; Alfian Mustofa (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2021)
This study aims to assess the quality of microbiology which includes the number of bacteria, mould, gram-positive and gram-negative bacteria found in broiler chicken litter kept in closed-house. The material used is chicken litter taken from 15 farms in Demak (0-100 masl), Semarang (100-300 masl), and Kendal (300-500 masl). This study used a completely randomized design (CRD) with 3 treatments and 5 replications. The results showed that height had a significant effect (P <0.01) on total bacteria and mould in broiler chicken litter. The types of gram-positive bacteria found in the chicken litter are rods (Lactobacillus, and Bacillus), round stems (Clostridium), and coccus (Streptococcus thermophilus). A type of gram-negative bacteria found on rod-shaped stretchers belong to the Coliform and Pseudomonas families. The conclusion of this study is that land elevation has an effect on the microbiological quality of broiler chickens kept in closed cages.